Performance Comparison of Mussel and Clam Shell Wastes As An Abrasive Agent Under Different Tooth Brushing Parameter - Hassan, Irna Syafika; Sanusi, Shahmir Hayyan (Research Progress in Mechanical and Manufacturing Engineering, 2022)
There are various types of abrasive particles used in toothpaste which contributes to the second-highest particle composition in a toothpaste. Around 10%- 40% of the toothpaste consist of abrasive ingredient that is used to mechanically remove the extrinsic stain from the tooth surface. Calcium carbonate has been used for a decade as an abrasive agent in toothpaste. In regards to calcium carbonate, mussel shell and clamshell showed a high calcium carbonate content, which has the potential to be used in the formulation of medicine and toothpaste ingredients. Therefore, this study investigates the potential and performance of calcium carbonate obtained from mussel shell and clamshell as an abrasive agent in toothpaste and explore its efficiency under different toothbrushing parameters. The mussel shell and clamshell were milled and sieved to a maximum particle size of 63 µm. The powder obtained from mussel shell and clamshell were mixed with glycerol and water to form slurries. The brushing test was performed on the acrylic (PMMA) surface since it has good properties similar to artificial teeth by using Reciprocating Tooth Brushing Test Rig. The experimental result of scratch produced from mussel shell and clamshell abrasive particle was analyzed in terms of scratch pattern, scratch factor, and drag factor to identify the effective toothbrushing parameter. The experimental analysis highlighted that teeth cleaning efficiency can be achieved by using the shell waste particles under optimum brushing load (1.5 N) and high brushing cycle (50 cycles). Technically, it is possible to replace the commercial calcium carbonate (extracted from limestone) with calcium carbonate obtained from mussel and clamshells as an abrasive agent in toothpaste